The Elevation of Building Rights to Ownership Rights in Shophouses and Home Offices After the Enactment of Law Number 11 of 2020 Concerning Job Creation - Aristo, Erly; Pangestu, Nathania Putri; Pranata, Kristian (JURNAL USM LAW REVIEW, 2024)
This research aims to analyze the regulations regarding the elevation of land rights for dual-function residential buildings, specifically shophouses, as stipulated in Government Regulation Number 18 of 2021. The formulated problem statement is about the elevation of building rights for shophouses according to Government Regulation Number 18 of 2021. Beforehand, shophouses and home offices were only classified as buildings with a business function; the building Use rights on shophouses and home offices could not be upgraded to ownership rights. Based on the Decree of the State Minister of Agrarian Affairs/Head of the National Land Agency Number 6 of 1998, it is necessary to upgrade building use rights to ownership rights of buildings with residential functions only, as stated on the Building Construction Permit. This research was conducted using a normative juridical method through a statutory approach and a conceptual approach to see the existing arrangements regarding the issues raised and expert opinions related to these problems. The result of this research is that shophouses and office residences play a dual role, serving both residential and commercial functions. Government Regulation No. 18 of 2021 emphasizes that shophouses and office residences with building rights can be upgraded to full ownership rights upon the rights holder's request by fulfilling the specified requirements.